Birth and Growth of Neuroimaging and Vascular Intervention at Sree Chitra Tirunal Institute for Medical Sciences & Technology, Thiruvananthapuram—Part I - Vedula, Rajanikanth Rao; Kolathu, Ravi Mandalam (Journal of Clinical Interventional Radiology ISVIR, 2021)
This article is a historical narrative that traces the growth of neuroradiology and interventional radiology at the Sree Chitra Tirunal Institute of Medical Sciences and Technology, Thiruvananthapuram. From its humble origins in the pre-CT scan era of the mid and late 1970s, when invasive diagnostic procedures such as percutaneous carotid angiography, myelography, pneumoencephalography (PEG) and ventriculography were the mainstay of neuroimaging, the authors take the reader through their gradual foray into catheter four-vessel angiography and later free-flow embolization of arteriovenous malformations (AVMs), and finally to the use of microcatheters for selective embolization procedures. The equipment used in those early years—fluoroscopic tilting table, roll-film cameras, serial changers, PEG tables—provide an insight to an era with all its challenges before the advent of digital imaging. The authors’ efforts to indigenize some of the hardware such as metallic stents and embolization material such as hydrogel spheres and lyophilized dura are also highlighted. The development of peripheral vascular intervention alongside neuroradiology is also highlighted. The authors pay tribute to an early pioneer of neuroradiology in India, Prof. Mahadevan Pillai, who was a guiding light to them during those nascent years.
Keywords: neuroimaging; vascular intervention; interventional neuroradiology